Identifikasi Pengembangan Koperasi Di Jawa Barat Berdasarkan Persfektif Jenis Usaha Tahun 2020-2022 - Dwi Putriana Nuramanah Kinding; Muhamad Solekan; M. Aris Pujiyanto; Sarno Sarno (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The role of cooperatives in supporting the economy is reflected in their contribution to GDP, which experiences a positive trend every year. The potential of each region is different, resulting in a classification of the types of cooperative businesses that exist in order to realize regional growth in accordance with the resources it has. This research uses descriptive research with a quantitative approach using the Location Quotient (LQ) method. The data used is secondary data obtained from the Ministry of Cooperatives and BPS West Java. The results of the Location Qoutient (LQ) method analysis show that two types of business are categorized as potential bases, namely the consumer cooperative and producer cooperative sectors, because they have an LQ value> 1. Meanwhile, the cooperative, service, marketing cooperative and savings and loan cooperative sectors are in a non-base position, because they have an LQ value <1.